The Odd Couple: Replacement Therapy for Citrate Transporter Deficiency in the Brain and the Liver - Sara Eyal (Epilepsy Currents, 2026)
AAV-mediated gene therapy in a model of SLC13A5 citrate transporter disorder rescues epileptic and metabolic phenotypes Bailey LE, Adams RM, Schackmuth MK, Garza IT, Knight K, Holmes SK, Eller MM, Lee M, and Bailey RM. J Clin Invest . 2026 Feb 19;136(8):e197503. doi: 10.1172/JCI197503. PMID: 41712282; PMCID: PMC13078891. SLC13A5 citrate transporter disorder is a rare epileptic encephalopathy caused by loss-of-function pathogenic variants in the SLC13A5 gene. Loss of sodium/citrate cotransporter function causes a severe early-life epilepsy resulting in lifelong developmental disabilities and increased extracellular citrate. Current antiseizure medications may reduce seizure frequency, yet more targeted treatments are needed to address the epileptic and neurodevelopmental SLC13A5 phenotype. We performed preclinical studies in SLC13A5-deficient (KO) mice evaluating phenotype rescue with adeno-associated virus (AAV) vector carrying a functional copy of the human SLC13A5 gene (AAV9/SLC13A5). Cerebrospinal fluid delivery of AAV9/SLC13A5 decreased extracellular citrate levels, normalized electrophysiologic and sleep architecture abnormalities, and restored resistance to chemically induced seizures and death. Treatment benefits were achieved with administration during early brain development and in young adult mice, indicating therapeutic efficacy across developmental and postdevelopmental stages. Comparison of delivery routes in young adult KO mice showed that higher brain targeting achieved with intracisterna magna delivery resulted in greater treatment benefit as compared with intrathecal lumbar puncture delivery. Together, these results support further development of AAV9/SLC13A5 for treating SLC13A5 citrate transporter disorder.